THE STUDENTS’ COMMUNICATION STRATEGIES: WHAT AND HOW? - Katharina Rustipa (Dinamika Bahasa dan Budaya, 2009)
English is a foreign language for the Indonesian learners. Although they have learned English for years, it is still foreign for them. They still find problems maintaining their conversation. In this article, the writer wants to report the English the students use in oral communication and how they use the communication strategies.The data were obtained by means of recording 3 conversations produced by 7 students  of  UNISBANK  Semarang  during the Speaking IV lesson. The unit of analysis in the current study is  turn. Every turn is observed to find out the communication strategies employed. Then, the reasons for employing the communication strategies are explained by using  Tarone’s theory. The result of the study shows that the communication strategies employed by the English Department students of UNISBANK in speaking English are: translation strategy: language switch strategy, word coinage strategy, appeal for assistance strategy, circumlocution strategy. The literal translation strategy dominates the strategies used by the English learners. Based on the findings, some suggestions are put forward as follows: the English learners should enrich their knowledge about the English rule and English vocabulary, Speaking teachers should introduce the communication strategies to the students. Key words: communication strategy, learning strategy, production strategy, translation strategy: language switch strategy, word coinage strategy, appeal for assistance strategy, circumlocution strategy.